2019 IEEE 39th International Conference on Distributed Computing Systems (ICDCS) 2019
DOI: 10.1109/icdcs.2019.00130
|View full text |Cite
|
Sign up to set email alerts
|

Adversarial Learning Attacks on Graph-based IoT Malware Detection Systems

Abstract: The main goal of this study is to investigate the robustness of graph-based Deep Learning (DL) models used for Internet of Things (IoT) malware classification against Adversarial Learning (AL). We designed two approaches to craft adversarial IoT software, including Off-the-Shelf Adversarial Attack (OSAA) methods, using six different AL attack approaches, and Graph Embedding and Augmentation (GEA). The GEA approach aims to preserve the functionality and practicality of the generated adversarial sample through a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 29 publications
0
45
0
Order By: Relevance
“…Table 1). Detailed discussion regarding OSAA can be found in [1]. • GEA: This approach is designed to generate AE that fools the classifier, while preserving the functionality and practicality of the original sample.…”
Section: Evaluation and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1). Detailed discussion regarding OSAA can be found in [1]. • GEA: This approach is designed to generate AE that fools the classifier, while preserving the functionality and practicality of the original sample.…”
Section: Evaluation and Discussionmentioning
confidence: 99%
“…ACM ISBN 978-1-4503-6726-4/19/05. https://doi.org/10.1145/3317549.3326296 little research work done on understanding the impact of AL on DLbased IoT malware detection system and practical implications [3], particularly those that utilize CFG features for detection [1]. Goal of this study.…”
Section: Introductionmentioning
confidence: 99%
“…Existing research scheme improved the performance of the topology of network without modifications in the structure of distributed nodes. Moreover, we observed that the GEA strategy is definitely capable to mis-classify all IoT malware samples as benign [9]. The attack chart analysis methodology includes three primary levels: (1) network and vulnerability scanning, (2) threat modeling.…”
Section: Figure 1-illustration Of Attack Graph [7]mentioning
confidence: 99%
“…This recognition method can also reduce the detection range, increase recognition accuracy, and improve the robustness and scalability of the detection program [10]. Botnets such as Mirai have utilized insecure consumer IoT products to conduct distributed denial of services (DDoS) events on essential Internet infrastructure [9].…”
Section: Figure 1-illustration Of Attack Graph [7]mentioning
confidence: 99%
“…However, similar to Convolutional Neural Networks (CNNs), GNNs are also vulnerable to adversarial attacks, one of which is the backdoor attack. Since GNNs are used increasingly more for security applications [1], it is important to study the backdoor attack on GNNs. Otherwise, security concerns will remain.…”
Section: Introductionmentioning
confidence: 99%